INTERNALIZATION OF ISLAMIC RELIGIOUS EDUCATION VALUES IN FORMING STUDENT CHARACTER - Mahdia, Sholehatun; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is motivated by the foundation of character formation in students. In the context of internalizing the values of Islamic religious education, schools play a central role in delivering religious teachings comprehensively and impartially, as well as implementing these values in the daily lives of students. The research questions in this study are: 1) How is the internalization of Islamic values in shaping the character of students at SMP Nurul Jadid? 2) What are the supporting and inhibiting factors in the internalization of Islamic values in shaping the character of students at SMP Nurul Jadid? The research method employed is field research using a qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and verification. The subjects of this study are the school principal and religious teachers at SMP Nurul Jadid. The results of this research are: 1) In-depth religious teaching, role modeling by teachers and staff, religious practices, appreciation of social and humanitarian values, and mental and spiritual guidance are crucial points in the internalization of Islamic values shaping students' characters. 2) Supporting factors include an Islamic school environment, an Islam-based curriculum, the role of teachers and staff, and extracurricular activities. Inhibiting factors involve the influence of the external environment, limited parental involvement, and curriculum mismatch.